Evaluation of the Safe Ischemic Time of Clamping During Intermittent Pringles Maneuver in Rabbits - Kolahdoozan; Behdad; Hosseinpour; Behdad; Rezaei (Archives of Trauma Research, 2015)

(untitled)
Background The liver is the most commonly injured organ in blunt abdominal trauma. Although major hepatic bleeding may be partially controlled with portal triade clamping (the Pringle’s maneuver), continuous prolonged clamping results in liver ischemia.